A Comparison of the Query Execution Algorithms in Secure Database System - Young-Dal Jang; Ji-Hong Kim (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In accordance with the database management, DAS(Database as Service) model is one solution for outsourcing. However, we need some data protection mechanisms in order to maintain the database security The most effective algorithm to secure databases from the security threat of third party attackers is to encrypt the sensitive data within the database. However, once we encrypt the sensitive data, we have difficulties in queries execution on the encrypted database. In this paper, we focus on the search process on the encrypted database. We proposed the selective tuple encryption method using Bloom Filter which could tell us the existence of the data. Finally, we compare the search performance between the proposed method and the other encryption methods we know.